The contribution of physical therapy in the recovery of the post-traumatic sequels of the hand and its influence regarding the resume of daily activity - Breha Alexandru Mihai (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
The traumas occurring at the level of the fist joint make the functions of the hand to be greatly diminished, thus we encounter a low coefficient of the patients' quality of life. The hand cannot be replaced in the daily needs of the human being, thus overloading occurs. [1]. This study, followed the selection of the most effective physical therapy techniques in addition to the electrotherapeutic program, to relieve pain, increase joint mobility, increase muscle strength and reintegrate patients into social/professional activity as quickly as possible. Electrotherapy, physical therapy and massage were applied to the 39 patients, the objectives of the therapeutic plan being adapted according to the patient's daily lifestyle. Following this study, we demonstrated that by selecting effective physiotherapy techniques we obtained long-term results, we reduced the risk of recurrence of traumatic conditions at the level of the fist joint, with patients registering improvements in the functional index of the hand.